On the Synthesis of Antibiotics for Agriculture - Normatov Anvar Mirzayevich; Nurmukhamedova Vazira Zahriddinovna; Niyozov Xasan Niyoz O’g’li; Ashurov Oybek Norboy O’g’li; Otajonov Asadbek Shonazar O’g’li; Yusupov Axliddin O’tkir O’g’li (Peerian Journals Publishing, 2022)
Traditional concepts about antibiotics or antibiotics have emerged due to their application in modern medicine and veterinary practice. Some antibiotic preparations are used to stimulate animal growth, combat plant diseases, while others are used to conserve food and conduct research (in the fields of biochemistry, molecular biology, genetics, oncology).
Keywords: Antibiotics; medicine; stimulation; conservation